2019
DOI: 10.15420/aer.2019.28.2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding AF Mechanisms Through Computational Modelling and Simulations

Abstract: AF is a progressive disease of the atria, involving complex mechanisms related to its initiation, maintenance and progression. Computational modelling provides a framework for integration of experimental and clinical findings, and has emerged as an essential part of mechanistic research in AF. The authors summarise recent advancements in development of multi-scale AF models and focus on the mechanistic links between alternations in atrial structure and electrophysiology with AF. Key AF mechanisms that have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 116 publications
(149 reference statements)
0
14
0
Order By: Relevance
“…We have reached a new era in minimising X-ray radiation exposure, with new ideas and novel technologies still to be developed in the future. 46,47…”
Section: Our Perspectivesmentioning
confidence: 99%
“…We have reached a new era in minimising X-ray radiation exposure, with new ideas and novel technologies still to be developed in the future. 46,47…”
Section: Our Perspectivesmentioning
confidence: 99%
“…Computational modeling has advanced in its ability to shed light on the knowledge of AF. This topic, however, lies beyond the scope of this review and is well reviewed elsewhere 57–60 . Since the first discovered mutation related to AF, S140G, advancements in genetic (mutations related to ion channels, cardiogenesis, and fibrosis) and epigenetic (microRNAs, long non‐coding RNAs) modifications have shed light on the relationship between DNA and AF 23 .…”
Section: Pathophysiological Mechanisms Of Af Related To Eatmentioning
confidence: 99%
“… 24 In silico studies also demonstrated that AF-promoting atrial repolarization alternans might occur due to decreased RyR inactivation, and that calcium-driven repolarization alternans due to AF-associated electrical remodelling increased the vulnerability to ectopy-induced arrhythmia. 12 , 68 , 69 Finally, in silico models of human atrial cardiomyocytes 75 , 118 , 120 have been used to study the impact of AF-related ion-channel remodelling 70–74 and remodelling associated with AF risk factors. 59 Until recently, most computational studies employed a single deterministic model, reflecting a representative atrial cardiomyocyte, thereby disregarding experimentally observed variability.…”
Section: The Role Of Mechanistic Models To Improve Understanding and Management Of Afmentioning
confidence: 99%